2009
DOI: 10.1128/iai.00814-08
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Persistent Colitis by a Human Commensal, Enterotoxigenic Bacteroides fragilis , in Wild-Type C57BL/6 Mice

Abstract: Enterotoxigenic Bacteroides fragilis (ETBF) causes diarrhea and is implicated in inflammatory bowel diseases and colorectal cancer. The only known ETBF virulence factor is the Bacteroides fragilis toxin (BFT), which induces E-cadherin cleavage, interleukin-8 secretion, and epithelial cell proliferation. A murine model for ETBF has not been characterized. Specific pathogen-free (SPF) C57BL/6J or germfree 129S6/SvEv mice were orally inoculated with wild-type ETBF (WT-ETBF) strains, a nontoxigenic WT strain of B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
242
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(256 citation statements)
references
References 62 publications
11
242
1
2
Order By: Relevance
“…In addition, inhibition of SMO by MDL 72527 in ETBF-infected mice was shown to (i) reduce chronic intestinal inflammation and proliferation; (ii) decrease the chronic up-regulation of cytokines associated with the Th17 immune response; and, most importantly, (iii) significantly inhibit colon tumorigenesis in Min mice. The results of these studies are particularly intriguing because, in contrast to other published models of intestinal carcinogenesis that rely on chemical irritants, mutagens, and/or immunocompromised mice, the ETBF model used for these experiments incorporates a genetic defect, a bacterial pathogen, and disease physiology that have direct importance in and therefore should be more applicable to human intestinal inflammation and colorectal cancer (12,13,16).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, inhibition of SMO by MDL 72527 in ETBF-infected mice was shown to (i) reduce chronic intestinal inflammation and proliferation; (ii) decrease the chronic up-regulation of cytokines associated with the Th17 immune response; and, most importantly, (iii) significantly inhibit colon tumorigenesis in Min mice. The results of these studies are particularly intriguing because, in contrast to other published models of intestinal carcinogenesis that rely on chemical irritants, mutagens, and/or immunocompromised mice, the ETBF model used for these experiments incorporates a genetic defect, a bacterial pathogen, and disease physiology that have direct importance in and therefore should be more applicable to human intestinal inflammation and colorectal cancer (12,13,16).…”
Section: Resultsmentioning
confidence: 91%
“…Recent studies have demonstrated that ETBF infection alone is necessary and sufficient to induce acute and persistent colitis in wild-type C57BL/6 mice (12,13). On the basis of these results, Wu and colleagues (14) studied the effect of ETBF on tumor formation in multiple intestinal neoplasia (Min) mice.…”
mentioning
confidence: 99%
“…miR-126 expression is often downregulated in cancers and is able to decrease leukocyte and possibly cancer cell adherence to endothelial cells by targeting VCAM-1 on endothelial cells [83]. Additionally, a number of miRNAs have been discovered to play critical roles in modulation of T and B lymphocytes activation, innate and adaptive immune responses [96,97]. For example, miR-155 is required in conventional and regulatory T lymphocyte differentiation/activation, B lymphocyte development, mac-rophage response and toll-like receptors (TLR) response through targeting suppressor of cytokine signaling 1 (SOCS1), activation-induced cytidine deaminase (AID) and transcription factor c-Maf [96][97][98].…”
Section: Mirnas Modulate Cancer Cell Survival and Arrest In The Circumentioning
confidence: 99%
“…Additionally, a number of miRNAs have been discovered to play critical roles in modulation of T and B lymphocytes activation, innate and adaptive immune responses [96,97]. For example, miR-155 is required in conventional and regulatory T lymphocyte differentiation/activation, B lymphocyte development, mac-rophage response and toll-like receptors (TLR) response through targeting suppressor of cytokine signaling 1 (SOCS1), activation-induced cytidine deaminase (AID) and transcription factor c-Maf [96][97][98]. miR-223 is found to have crucial roles in regulating granulocyte proliferation and activation by regulating myeloid ELF-1-like factor (Mef2c) [99].…”
Section: Mirnas Modulate Cancer Cell Survival and Arrest In The Circumentioning
confidence: 99%
See 1 more Smart Citation